Measuring the relative hydrogen-bonding strengths of alcohols in aprotic organic solvents - Lee, Melvyn (2015)
Voltammetric experiments with 9,10-anthraquinone and 1,4-benzoquinone performed under controlled moisture conditions indicate that the hydrogen-bond strengths of alcohols in aprotic organic solvents can be differentiated by the electrochemical parameter ΔEpred=|Epred(1)−Epred(2)|, which is the potential separation between the two one-electron reduction processes. This electrochemical parameter is inversely related to the strength of the interactions and can be used to differentiate between primary, secondary, tertiary alcohols, and even diols, as it is sensitive to both their steric and electronic properties. The results are highly reproducible across two solvents with substantially different hydrogen-bonding properties (CH3CN and CH2Cl2) and are supported by density functional theory calculations. This indicates that the numerous solvent–alcohol interactions are less significant than the quinone–alcohol hydrogen-bonding interactions. The utility of ΔEpred was illustrated by comparisons between 1) 3,3,3-trifluoro-n-propanol and 1,3-difluoroisopropanol and 2) ethylene glycol and 2,2,2-trifluoroethanol.